Enhancing cultural sensitivity in the implementation of the Fertility Quality of Life Tool in Sudan: a science diplomacy perspective - Bayoumi, Rasha R.; Koert, Emily; Boivin, Jacky; McConnell, Margaret; Wolde, Betelhem; Siddiqui, Fatima; Elmusharaf, Khalifa; Viswanath, Kasisomayajula (Frontiers in Public Health, 2024)
Background: Infertility is a global health challenge affecting quality of life, especially in low and middle-income countries like Sudan. The Fertility Quality of Life (FertiQoL), a standardized questionnaire, pivotal in evaluating fertility-related quality of life. However, research on its utility has primarily focused on Global North and High-Income Countries, highlighting the need to shift away from neocolonialism to promote truly inclusive research and effective healthcare practices. Science diplomacy, achieved through culturally sensitive tool implementation, can catalyze addressing global health disparities. This study assesses methodological and cultural considerations impacting FertiQoL tool implementation in Sudan within the framework of science diplomacy, contributing to the broader discussion on decolonizing global health research. Methods: Employing explanatory sequential design with surveys and interviews, in a Sudanese fertility clinic (November 2017 - May 2018), using convenience sampling, we recruited 102 participants. We collected socio-demographic, medical, and reproductive history data. The Arabic FertiQoL was administered, with 20 interviews and 82 surveys (40 self-administered, 42 provider-administered). Descriptive statistics, one-way ANOVA, thematic analysis, and triangulation were used to explore methodological and cultural nuances. Results: Most participants, were educated urban women. ANOVA results revealed no statistically significant differences in FertiQoL scores based on the mode of administration [core score (F(2,99)=1.58, p=.21, η2=.03) domain scores: emotional (F(2,99)=1.85, p=.16, η2=.04); mind/body (F(2,99)=1.95, p=.15, η2=.04); relational (F(2,99)=0.18, p=0.83, η2=.04); and social (F(2,99)=1.67, p=0.19, η2=.03)]. Qualitative insights revealed vital cultural considerations such as interpretation of concepts like hope and jealousy. Notably, the FertiQoL social domain was found to inadequately capture the social pressures experienced by infertile individuals in Sudan, underscoring the importance of region-specific research. Despite these challenges, participants perceived FertiQoL as a comprehensive and valuable tool with broader utility beyond assessing fertility-related quality of life. Discussion: Our findings emphasize the significance of culturally sensitivity interpretation of FertiQoL scores when implementing it globally. This approach aligns with science diplomacy principles and challenges neocolonial structures by acknowledging the unique lived experiences of local populations. Fostering cross-cultural understanding and inclusivity in research, can enhance implementation of FertiQoL and pave the way for novel interventions and policy developments in the Global South, ultimately promoting equitable global health.